ChemInform Abstract: A Copper‐Mediated Oxidative N‐Cyanation Reaction. Issue 51 (23rd December 2014) - Teng, Fan; Yu, Jin‐Tao; Jiang, Yan; Yang, Haitao; Cheng, Jiang
Abstract The oxidative coupling of sec‐amines (I), (IV), and (VI) with CuCN gives rise to a series of N‐cyanation products in moderate to high yields.